ANÁLISE DA PRODUTIVIDADE E DO CUSTO ENTRE O SISTEMA DE PRODUÇÃO COM ARGAMASSA ESTABILIZADA, PREPARADA EM OBRA E A PRODUZIDA COM ARGAMASSA INDUSTRIALIZADA - Angelim, Vanessa Lira; Heineck, Luiz Fernando Mählmann (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research works coastwise evaluates the performance of three different methods of mortar production for bricklaying. Typical on site production of local mortar mixing sand, lime and cement is compared to the supply of premixed 25 kg bags of those materials and stabilized premixed mortar paste in terms of manpower consumption both for bricklaying and mortar mixing and distribution. The research method was a case study in a building site located in the city of Fortaleza, Ceará. Apart from that, material and equipment costs for mixing and transportation were taken into consideration. RUP productivity assessment methodology indicates that man hours in connection to mortar supply are reduced to a third but total costs are very similar, due to the commercial costs of more industrialized materials. This research advocates a stronger commercial bargaining power for building companies and scale economies in order to make cost significant advances in building production, taking advantage of the already achieved productivity improvements put forward by more industrialised methods of mortar supply.